RESOLUTION OF GESTATIONAL GIGANTOMASTIA WITH TERMINATION OF PREGNANCY - Bukhari, Syed Sarmad; Manan, Haris; Khan, Mah Muneer; Raza, Syed Shahmeer (Journal of Ayub Medical College Abbottabad, 2018)
Less than 100 cases of gestational gigantomastia have been described in literature. The aetiology and risk factors are not well-established. Various treatments have been used with some consensus. We present the case of a 47-year-old female who presented to us with bilateral gigantomastia in her 16th week of gestation. She had massively enlarged breasts which were very painful. Relevant laboratory investigations were normal. An incisional biopsy done prior to, and two trucut samples at presentation to us, showed normal breast tissue proliferation. In the absence of adequate pain control, it was decided to electively terminate the pregnancy and give a trial of tamoxifen. She made a rapid recovery following termination without requiring the use of tamoxifen Keywords: Gigantomastia; Pregnancy; Gestational gigantomastia